THE EFFECT OF ENTREPRENEURIAL EDUCATION AND ENTREPRENEURIAL SELF- EFFICACY WITH ENTREPRENEURIAL MINDSET AS AN INTERVENING VARIABLE ON ENTREPRENEURIAL INTENTION - Welly Ervina Solissa; M. Rasyid Ridha; Firdaus W. Suhaeb (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2026)
The lack of Vocational High School graduates who have entrepreneurial intentions and can create new businesses is where the role of entrepreneurship education is needed, which is expected to provide valuable experience to offer entrepreneurial activities; mindset and self- efficacy also significantly affect the formation of entrepreneurial behaviour. To forecast and validate the stated hypothesis, this study employs a quantitative methodology using partial least squares structural equation modeling (PLSSEM). Data about Mojokerto Regency vocational students was gathered for this study using Google Forms. 162 respondents from the three research-objective schools participated in this study. Self-efficacy, entrepreneurial attitude, and entrepreneurship education may all have an impact on entrepreneurial intention, according to the research.